Pre-deposited dynamic membrane filtration - a review - Anantharaman, Aditya (2022)
A dynamic membrane (DM) is a layer of particles deposited via permeation drag onto a conventional membrane, such that the deposited particles act as a secondary membrane that minimizes fouling of the primary membrane to lower transmembrane pressures (TMP) and enable higher permeate fluxes. Since the first DM was created in 1966 at the Oak Ridge National Laboratory, numerous studies have reported synthesis of DMs using various materials and explored their abilities to perform reverse osmosis (RO), nanofiltration (NF), ultrafiltration (UF) and microfiltration (MF). DMs are classified into two categories, namely, (i) self-formed, whereby the feed constituents form the DM; and (ii) pre-deposited, whereby the DM is formed by a layer of particles other than the feed prior to introduction of the feed. This paper endeavors to present a comprehensive review of the state-of-the-art on the latter. Key materials used as DMs, their formation and various factors influencing it, regeneration of DMs and modifications to DM systems for performance enhancement are discussed. The role of DMs in preventing fouling in the primary membrane (PM) is explained. The applications of DMs in four major areas, namely, salt and organic solute rejection, treatment of industrial effluents, treatment of water and wastewater, and oily-wastewater treatment are reviewed. Furthermore, technical and economic advantages of DMs over conventional processes are considered, and challenges in current DM research are discussed. Finally, directions for future research are suggested.